2017
DOI: 10.3390/brainsci7070084
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Neuroimaging of Visual Hallucinations in Lewy Body Disease: A Systematic Literature Review

Abstract: Patients with Lewy body disease (LBD) frequently experience visual hallucinations (VH), well-formed images perceived without the presence of real stimuli. The structural and functional brain mechanisms underlying VH in LBD are still unclear. The present review summarises the current literature on the neural correlates of VH in LBD, namely Parkinson’s disease (PD), and dementia with Lewy bodies (DLB). Following a systematic literature search, 56 neuroimaging studies of VH in PD and DLB were critically reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 108 publications
(437 reference statements)
3
39
2
Order By: Relevance
“…These functional attributes of the memory perception network and the enhancement of its activity may be involved in the generation of visual hallucination in DLB. Contrary to our results, many previous DLB studies reported visual hallucination patients in association with worse visuospatial and cognitive function compared with patients without visual hallucination [94, 95]. However, while we used drug-free early-stage DLB patients, in these studies, visual hallucination patients tended to have more advanced stage of the disease than patients without visual hallucination and were treated with drugs such as AchEI, levodopa, and antipsychotics, which affect DLB symptoms and brain functions.…”
Section: Discussioncontrasting
confidence: 99%
“…These functional attributes of the memory perception network and the enhancement of its activity may be involved in the generation of visual hallucination in DLB. Contrary to our results, many previous DLB studies reported visual hallucination patients in association with worse visuospatial and cognitive function compared with patients without visual hallucination [94, 95]. However, while we used drug-free early-stage DLB patients, in these studies, visual hallucination patients tended to have more advanced stage of the disease than patients without visual hallucination and were treated with drugs such as AchEI, levodopa, and antipsychotics, which affect DLB symptoms and brain functions.…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, the expression of the CIS (and thus its value to increase FDG PET specificity) varies across different stages of the disease and can be utilized for diagnostic purposes mainly in the mild stages. [30][31][32] Despite the relatively high number of patients, we could not directly compare subgroups according to individual core feature because "pure" subgrouping was hampered by the very low number of patients presenting only 1 core feature, as is the common clinical presentation of DLB. The evidence of relatively spared MTL metabolism is in keeping with several magnetic resonance imaging (MRI) studies evaluating pattern of atrophy in DLB and suggests that this finding may increase the specificity of the differential diagnosis between AD and DLB across most disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…1 Similarly, relatively increased striatal metabolism was previously described early in the disease course in Parkinson disease (PD) patients but not in atypical parkinsonian syndromes. 32 Given the established role of FDG PET as a marker of metabolic functional connectivity, the ipsilateral left-sided frontal and parietal negative covariance with VH could be interpreted as a sign of frontoparietal disconnection. The present findings underline the metabolic similarities and thus the potential continuum within the clinical spectrum ranging from PD to DLB.…”
Section: Discussionmentioning
confidence: 99%
“…The functional connectivity between brain regions can be measured with a single functional MRI scan. The pattern of the default mode network is potentially relevant in characterization and diagnosis of neurologic disorders . Horizontal networks are also effectively analyzed with neurophysiologic tools.…”
Section: Acting Globally In a Complex Systemmentioning
confidence: 99%
“…The pattern of the default mode network is potentially relevant in characterization and diagnosis of neurologic disorders. [45][46][47] Horizontal networks are also effectively analyzed with neurophysiologic tools. High-frequency oscillations (HFOs) are studied as an emergent property of either physiologic or pathologic neuronal interactions within a horizontal micronetwork.…”
Section: Acting Globally In a Complex Systemmentioning
confidence: 99%